Secondary access to the radar spectrum bands: Regulatory and business implications - Evanny Obregon; Ki Won Sung; Jens Zander (International Telecommunications Society (ITS), 2013)
The large expected increase in the capacity requirements raises not only technical issues but also regulatory and business challenges. One of the key methods to increase the capacity of mobile networks in a cost efficient way is to find additional frequency spectrum. However, it is a difficult task since most of the spectrum is already allocated in long-term basis. Therefore, innovation in the technical and regulatory domain is needed to make additional spectrum available for mobile communications that not only improve spectrum utilization but also to make long-term investments feasible. Secondary spectrum access was proposed as a technical solution to improve spectrum utilization. However, uncertainties on the regulatory regime have been the main 'show-stopper' for long-term investments. This paper has devised techno-regulatory conditions for making large-scale secondary access to the radar bands an attractive business scenario from the MNO's perspective. Our numerical results showed that applying regulation on the deployment of secondary users can significantly improve sharing opportunities, especially in lower frequency bands (S-band) where the impact of interference aggregation is higher. We also identified Licensed Shared Access (LSA) as suitable authorization model for secondary access to the radar bands since it provides the level of reliability on the protection against harmful interference and it could also motivate long-term investments. Finally, establishing the right spectrum access cost or license fee for secondary access to the radar bands is crucial for achieving competitive edge over alternatives indoor solutions.
Keywords: 330